2013
DOI: 10.1007/jhep07(2013)114
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the standard model Higgs signal with the Template Overlap Method

Abstract: We show that the Template Overlap Method can improve the signal to background ratio of boosted h → bb events produced in association with a leptonically decaying W . We introduce several improvements on the previous formulations of the template method. Varying three-particle template subcones increases the rejection power against the backgrounds, while the longitudinally invariant, sequential template generation ensures an efficient coverage in template phase space. We integrate b-tagging information into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 49 publications
2
49
0
Order By: Relevance
“…The techniques of jet substructure, which exploit the internal structure of the jet, have been developed for this task. Contemporary experimental and theoretical work in the field of jet substructure includes, but is not limited to, subjet finding and jet tagging / jet flavor identification algorithms [2][3][4][5][6][7][8][9][10][11][12], jet grooming and pileup mitigation [13][14][15], template and matrix element techniques [16,17], energy flow and event shapes [18][19][20][21][22][23][24], and probabilistic jet clustering [25,26]; more inclusive summaries can be found in references [27][28][29][30] Typical approaches to jet flavor identification and jet tagging begin with a simplified analytic expression of the system's behavior, such as the two-pronged nature of the hadronic W boson decay, or the large particle multiplicity of gluon initiated jets relative to quark initiated jets. A variable which capitalizes on this analytic knowledge and is ideally not subject to large theoretical uncertainties is derived.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques of jet substructure, which exploit the internal structure of the jet, have been developed for this task. Contemporary experimental and theoretical work in the field of jet substructure includes, but is not limited to, subjet finding and jet tagging / jet flavor identification algorithms [2][3][4][5][6][7][8][9][10][11][12], jet grooming and pileup mitigation [13][14][15], template and matrix element techniques [16,17], energy flow and event shapes [18][19][20][21][22][23][24], and probabilistic jet clustering [25,26]; more inclusive summaries can be found in references [27][28][29][30] Typical approaches to jet flavor identification and jet tagging begin with a simplified analytic expression of the system's behavior, such as the two-pronged nature of the hadronic W boson decay, or the large particle multiplicity of gluon initiated jets relative to quark initiated jets. A variable which capitalizes on this analytic knowledge and is ideally not subject to large theoretical uncertainties is derived.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [17,18] showed that the effects of pileup are not significant on TOM (up to 50 pileup events). The low susceptibility to pileup is a manifest of the fact that, by construction, TOM is sensitive mostly to the hard energy depositions within the fat jet and less so to the incoherent soft radiation.…”
Section: Jhep09(2015)022mentioning
confidence: 98%
“…Our study adopts the Template Overlap Method (TOM) [15][16][17][18] to tag the highly boosted decay product of the partners and in part reject the corresponding SM backgrounds. The final state of our signal events is characterized by multiple b-jets, which we employ through a semi-realistic b-tagging procedure.…”
Section: Jhep09(2015)022mentioning
confidence: 99%
See 1 more Smart Citation
“…A typical value for c in a tt -spectrum measurement without jet substructure top tagging is about 20 % (c = 0.2) [24]. (This number, and the selection efficiency, are expected to change if top tagging through jet substructure [25] is used in the analysis.) Thus, we get that the systematic and statistical uncertainties are of the same order provided that N ∼ 1/c 2 ≈ O(10).…”
Section: Angular Distribution In Tt Productionmentioning
confidence: 99%